PEMANFAATAN LAYANAN REFERENSI DI UPT PERPUSTAKAAN IAIN BATUSANGKAR - Lailatur Rahmi; Rika Jufriazia Manita (IAIN Batusangkar, 2020)
University libraries exist to support the teaching , learning and research needs of their institution. This is done by providing the latest information sources for the academic community as university library users. This mission can be achieved well through effective and periodic marketing of information and library services, one of which is through reference services. This article discusses the use of reference and information services in supporting distance learning as one of the impacts of the spread of the Covid 19 outbreak (current situation and the way forward). The research method is quantitative descriptive research, with 78 respondents and using literature related to the transformation of reference services in the digital era. Data collection is processed based on the results of observations, interviews of the IAIN Batusangkar library reference service and other college libraries in providing online reference services. The analysis explains the presence of a reference service for students, especially Library Science students at IAIN Batusangkar. Analyzing how the media can help reference librarians in providing optimal services to the academic community remotely. Describe the strategies that reference librarians can use in creating real time reference transactions in a technology environment while maintaining the main function of reference services. Introducing the idea of a ‘new face’ model of reference and information services for the IAIN Batusangkar library in the period of distance learning, especially the rapid change in learning systems as a result of the corona virus outbreak ( covid 19). Libraries need to improve the reference service system they provide, so that the academic community can meet their information needs through library services remotely, anytime and anywhere. At the end of this paper, it is intended that librarians, especially reference librarians. Continue to serve readers with different needs, librarians must walk across the library, access computer screens from all campus intranet systems, answer emails and explore other interactive tools to reach customers in an effective, practical and effective way. Efficient in order to always satisfy users and keep closer to them, as the main purpose of the presence of reference services.